2020
DOI: 10.1136/bmjopen-2019-035037
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diseases and multimorbidity among unemployed and employed persons in the Netherlands: a register-based cross-sectional study

Abstract: ObjectivesThe first objective of this study was to describe the age-specific prevalence of chronic diseases and multimorbidity among unemployed and employed persons. The second objective was to examine associations of employment status and sociodemographic characteristics with chronic diseases and multimorbidity.DesignData linkage of cross-sectional nationwide registries on employment status, medication us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
(29 reference statements)
3
16
0
5
Order By: Relevance
“…Many studies have shown that chronic diseases, such as psychological disorders, cardiovascular diseases and diabetes, are typically more common among unemployed individuals ( 4 7 ) and are associated with a higher risk of being unemployed ( 8 ). However, most studies address loss of paid employment in the workforce rather than health as a barrier for (re)entering paid employment ( 9 ).…”
mentioning
confidence: 99%
“…Many studies have shown that chronic diseases, such as psychological disorders, cardiovascular diseases and diabetes, are typically more common among unemployed individuals ( 4 7 ) and are associated with a higher risk of being unemployed ( 8 ). However, most studies address loss of paid employment in the workforce rather than health as a barrier for (re)entering paid employment ( 9 ).…”
mentioning
confidence: 99%
“…Therefore, 31 studies can be considered largely atheoretical, without any emphasis on pathways through which socioeconomic disadvantage leads to multimorbidity. In the 33 studies applying a theory, the following theories were referred to: behavioural,10 34 35 37 38 40–42 46 51–53 59 71 72 79–82 materialist38 41 42 45 46 48 50 52 71 72 74 79 82–85 and psychosocial 34 42 51 52 57 72 73 82 84–86. In addition, four studies applied a theoretical construct called ‘sense of coherence’, which indicates an individual’s coping capacity to deal with life and stressful events,87 and is an indicator of self-efficacy and psychosocial well-being (consistent with psychosocial explanations),73 and also encompasses social capital51 and social support,57 which are widely considered as psychosocial assets (table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Dispensed medicines are classified into anatomic, therapeutic, chemical (ATC) classification codes, according to the WHO (World Health Organization) drug classification system of 2010 ( 16 ). Previous research has used these ATC codes to identify specific chronic diseases and estimate the prevalence among the working population ( 17 , 18 ). Following these definitions, six chronic diseases were identified: cardiovascular diseases, respiratory diseases, inflammatory diseases, diabetes, mental disorders (depressive, anxiety and sleep disorders) and psychotic disorders.…”
Section: Methodsmentioning
confidence: 99%